Altered tissue distribution in adults with cystic fibrosis - Bolton, C E; Ionescu, A A; Evans, W D; Pettit, R J; Shale, D J (Thorax, 2003)
Background: Regional body composition was determined in adults with cystic fibrosis (CF). Our hypothesis was that dual energy x ray absorptiometry (DXA) scanning could assess the fat free mass, bone mineral content, and fat mass and determine the distribution of the changes. Method: Height squared indices were derived for fat mass (FMI), fat free mass (FFMI), and bone mineral content (BMCI) of the arm, leg, and trunk by DXA in 51 patients and 18 age/sex matched healthy subjects. Results: The arm and leg FFMI in patients were less than in healthy controls (p<0.05); the deficit was leg>arm>trunk (−18.19%, −14.86%, +0.09%, p<0.02) and was related to severity of lung disease. Patients with a normal BMI and low total FFM (hidden loss) had a lower arm, leg and trunk FFMI than those with a normal BMI and total FFM (p<0.05). The BMCI for all body segments was lower in patients than in controls (p<0.001). The BMCI was lower in the leg and trunk (p<0.01) in patients with severe disease than in those with mild lung disease. In those with hidden FFM loss the BMCI was lower (p<0.05 in leg and trunk). There was no difference in the BMCI deficit between body segments. Fat mass in patients was not reduced. Conclusion: Preferential loss of FFM is related to severity of lung disease and occurs in patients with a normal BMI. A similar loss of BMC occurs while FM is preserved. A hierarchical pattern of FFM loss of legs>arms>trunk was shown; BMC loss was evenly distributed.